Answer:
idk the answer
Step-by-step explanation:
This equation is also equal to 3/4x - 2/3 + 5/6 + 2x since subtracting a negative is the same as adding a positive in the long run. First, simplify the variables to get 2 3/4x - 2/3 + 5/6. -2/3 is also equal to -4/6, so -4/6 + 5/6 is 1/6. The simplified version of this expression is 2 3/4x + 1/6. Hope this helps!
Answer:
b
Step-by-step explanation:
I know this is a stretch, but maybe the thickness of a nail?
<span>4x + 8 = −2 − 2 + 5x
5x - 4x = 8 + 4
x = 12
There's only one solution, x = 12</span>